Kepatuhan wajib pajak orang pribadi di Kabupaten Jember pasca pandemi covid-19 - Fidyaningrum, Mekar; Sulistiyanti, Umi (Proceeding of National Conference on Accounting & Finance, 2024)
Tax compliance is an action that must be owned by taxpayers where the action is in the form of awareness and compliance with laws and regulations regarding tax fulfillment obligations. This study outlines the causal factors that can affect tax compliance by using variables of tax administration system modernization, tax socialization, love of money, and trust in tax authorities. This study took a sample of individual taxpayers registered at KPP Pratama Jember as many as 125 respondents. Data collection techniques using manual questionnaires in the form of leaflets. Data processing uses SPSS 25 software that takes multiple linear regression models. The results of this study that modernization of the tax administration system, tax socialization, and trust in tax authorities had a positive effect on taxpayer compliance, while love of money had no effect on taxpayer compliance.